Protein engineering of a stable and potent anti-inflammatory IL-37-Fc fusion with enhanced therapeutic potential. Issue 4 (21st April 2022) - Bujotzek, Alexander; Tiefenthaler, Georg; Lariviere, Laurent; D'Andrea, Laura; Marquez, Elsa A.; Rudloff, Ina; Cho, Steven X.; Deen, Nadia S.; Richter, Wolfgang; Regenass-Lechner, Franziska; Poehler, Alexander; Whisstock, James C.; et al.
Summary: Harnessing the immunomodulatory activity of cytokines is a focus of therapies targeting inflammatory disease. The interleukin (IL)-1 superfamily contains pro-inflammatory and anti-inflammatory members that help orchestrate the immune response in adaptive and innate immunity. Of these molecules, IL-37 has robust anti-inflammatory activity across a range of disease models through inhibition of pro-inflammatory signaling cascades downstream of tumor necrosis factor, IL-1, and toll-like receptor pathways. We find that IL-37 is unstable with a poor pharmacokinetic and manufacturing profile. Here, we present the engineering of IL-37 from an unstable cytokine into an anti-inflammatory molecule with an excellent therapeutic likeness. We overcame these shortcomings through site-directed mutagenesis, the addition of a non-native disulfide bond, and the engineering of IL-37 as an Fc-fusion protein. Our results provide a platform for preclinical testing of IL-37 Fc-fusion proteins. The engineering approaches undertaken herein will apply to the conversion of similar potent yet short-acting cytokines into therapeutics. Graphical abstract: Highlights: We engineer an IL-37 Fc-fusion protein with an excellent therapeutic likeness Targeted deletion of cysteine residues enables high-capacity mammalian production Disulfide bond engineering drastically enhances the PK profile of IL-37-Fc These data provide a pathway to preclinical testing of IL-37 Fc-fusions Abstract : IL-37 has a poor pharmacokinetic and manufacturing profile. Here, Bujotzek et al. overcome these shortcomings through site-directed mutagenesis, non-native disulfide bond insertion, and engineering of IL-37 as an Fc-fusion protein. These approaches will apply to converting similar potent yet unstable cytokines into molecules with therapeutic likeness.